Pelatihan Calon Kepala Sekolah Berbasis Moda Daring Yayasan Pendidikan Kristen Kota Salatiga - Marinu Waruwu; Yari Dwikurnaningsih; Wasitohadi Wasitohadi; Bambang Ismanto; Ade Iriani; Sophia Tri Satyawati (Universitas Kristen Satya Wacana Salatiga, 2021)
Community service activities are carried out at the Central Christian Education Institution, Salatiga City. The objective of this activity is to prepare teachers who are selected as prospective principals to understand the concept and implementation of school principal competency standards in the fields of managerial, supervision, and entrepreneurship. Activities are held in the form of online mode-based training. The school development plan is the final product of this training activity. This activity is expected to create prospective school leaders of the Central Christian Education Institution Salatiga who can improve the quality of education through their leadership, creativity, and innovation qualities. The results of this community service activity can improve managerial competence, supervision, and entrepreneurship for prospective principals of the Christian Education Institution Salatiga.